Example-Based School Principal Leadership In Improving Teacher Performance (Multi Site Study of Almuslimin Pandan Private Middle School and Padan 1 Public Middle School, Central Tapanuli Regency) - Hutabarat, Samrul Bahri; Wijaya, Candra; Mardianto, Mardianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to 1) analyze the exemplary leadership of the principals of Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Tapanuli Tenga Regency, 2) analyze the performance of teachers of Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency, 3) analyze the results of exemplary the principal's leadership in improving the performance of teachers at Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency. This research uses qualitative methods and multiple approaches situs. Data was obtained through interviews, observation, documentation studies and Focus Group Discussions. Using two data analyzes namely: first, individual site data analysis is carried out through data reduction, data presentation, data verification. Second, cross- site data analysis is carried out as a process of comparing and integrating the results obtained from each site. The results of this research are: 1) Exemplary leadership of the principal of Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency, carrying out tasks on time and even arriving early and leaving later than the applicable hours. 2) The performance of teachers at Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency in terms of implementing rules and regulations, teachers have obeyed school rules and carried out tasks on time. 3) The results of the principal's exemplary leadership in improving the performance of teachers at Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency, namely increased teacher performance at Al Muslimin Pandan Private Middle School and Pandan 1 Public Middle School, Central Tapanuli Regency by seeking various forms of time discipline. Obey school rules, imitate subordinates by being humorous, and work professionally.